Cover Image, Volume 29, Issue 5. Issue 5 (15th April 2019) - Kyle, Colin T.; Stokes, Jared; Bennett, Jeffrey; Meltzer, Jeri; Permenter, Michele R.; Vogt, Julie A.; Ekstrom, Arne; Barnes, Carol A.
Abstract : Cover legend: This cover image is based on the Research Article Cytoarchitectonically‐driven MRI atlas of nonhuman primate hippocampus: Preservation of subfi eld volumes in aging by Colin T. Kyle et al., DOI:10.1002/hipo.22969 .